Preface to the Special Issue on “Computational Mechanics in Engineering Mathematics” - Michael R. Booty (Mathematics, 2023)
Increases in computational resources and the constant development of numerical methods have greatly expanded the range and complexity of systems that can be simulated numerically [...]